2022
DOI: 10.1002/edn3.314
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sample collection and storage protocols for surface eDNA surveys of an invasive terrestrial insect

Abstract: Environmental DNA surveys have revolutionized monitoring of rare or cryptic species and species inhabiting areas where conventional sampling is difficult or dangerous.Recent advancements within terrestrial environments include the capture of eDNA deposited by animals on surfaces such as tree bark and foliage, hereafter "surface eDNA." Notably, a technique which uses commercial paint rollers to aggregate surface eDNA has been deployed with success to detect the presence of forest insect pests providing a potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Mammals and potentially endangered species can also be detected using samples from natural saltlicks utilizing eDNA metabarcoding [ 104 ]. Using eDNA from the soil to trace mammals [ 105 ] is not only environment dependent but also dependent on mammal abundance and size [ 106 ]. Hence, knowledge of the ecological behavior of the mammal is essential for the sampling design [ 99 ].…”
Section: Exertion Of Environmental Dna In Terrestrial Ecosystemsmentioning
confidence: 99%
“…Mammals and potentially endangered species can also be detected using samples from natural saltlicks utilizing eDNA metabarcoding [ 104 ]. Using eDNA from the soil to trace mammals [ 105 ] is not only environment dependent but also dependent on mammal abundance and size [ 106 ]. Hence, knowledge of the ecological behavior of the mammal is essential for the sampling design [ 99 ].…”
Section: Exertion Of Environmental Dna In Terrestrial Ecosystemsmentioning
confidence: 99%
“…At the same time, the number of samples in eDNA-based studies could be reduced, at least in theory, by pooling samples. For example, Peterson et al (2022) demonstrated that multiple trees can be sampled using the same roller swab before detection probability of DNA is reduced. Thus, increasing the number of trees per sample, or even pooling bark and understory samples, at each site may have increased the efficiency and detection power of our survey.…”
Section: Discussionmentioning
confidence: 99%
“…We avoided field sample contamination by wearing clean gloves, bleach sterilizing rollers and frames prior to deployment, and transporting gear within sterile bags (see Appendix S1 for additional details). After sampling, we placed the roller into an 800 mL (304 × 114 mm) sterile bag, added deionized (DI) water until ~30–40% of the roller was submerged (~130 mL), and massaged the roller for 15 s within the bag to dislodge and suspend DNA into the water (Peterson et al., 2022). Finally, we removed the roller from the bag and filtered the remaining water through a 5 μm polycarbonate track‐etched (PCTE) membrane filter housed in a sterilized 47 mm plastic filter holder (Whatman Swin‐Lok, Cytiva, Marlborough, Massachusetts, USA) using a peristaltic field pump and silicone tubing.…”
Section: Methodsmentioning
confidence: 99%
“…(Valentin et al., 2020, 2021 ) and Peterson et al. (2022) have explored the feasibility of collecting eDNA in agricultural and forestry systems with sap‐sucking, phloem‐feeding insects that produce higher quantities of frass (i.e., honeydew). The viability of detecting these taxa in environmental samples is higher because of the higher abundance of eDNA.…”
Section: Discussionmentioning
confidence: 99%
“…As opposed to sampling eDNA in aquatic systems, sampling taxa in terrestrial systems using eDNA methodology is a developing field. Recent studies by Valentin et al (Valentin et al, 2020 and Peterson et al (2022) have explored the feasibility of collecting eDNA in agricultural and forestry systems with sap-sucking, phloem-feeding insects that produce higher quantities of frass (i.e., honeydew). The viability of detecting these taxa in environmental samples is higher because of the higher abundance of eDNA.…”
Section: A Anxiusmentioning
confidence: 99%